A novel non-stoichiometric medium-entropy carbide stabilized by anion vacancies. (15th August 2020) - Peng, Chong; Tang, Hu; He, Yu; Lu, Xiaoqian; Jia, Peng; Liu, Guoying; Zhao, Yucheng; Wang, Mingzhi
Abstract: Recently, high-entropy ceramics have attracted considerable attentions because of comprehensive physical and chemical properties of high hardness, fracture toughness, and conductivity. However, as a newly emerging class of materials, the synthesis, performance and applications of high-entropy ceramics are subject to further development. Here, we reported a new non-stoichiometric TiC0.4 /WC/0.5Mo2 C medium-entropy carbide (MEC) with a rock-salt structure. Attributed to the solid solution strengthening and twinning strengthening, the TiC0.4 /WC/0.5Mo2 C sintered at 1900 °C by spark plasma sintering (SPS) shows superior mechanical behaviors of microhardness (21.7 GPa), which exceeds that expected from the rule of mixture (ROM) of three individual metal carbides (19.1 GPa) and good fracture toughness (5.3 MPa m 1/2 ). Significantly, the bulk synthesized via high-pressure and high-temperature (HPHT) sintering possesses smaller grain size and shows better comprehensive mechanical properties of microhardness (23.7 GPa) and fracture toughness (6.2 MPa m 1/2 ). In addition, the effect of anion vacancies on the thermodynamic stability and synthesizability of TiC0.4 /WC/0.5Mo2 C was analyzed via quantitatively calculated entropy. Vacancies could significantly enhance the configurational entropy of mixing of the solid phase. The introduction of vacancy defects may expand synthetic path for entropy-stabilized ceramics, especially for multi-component high temperature refractory ceramics.